We over me : the counterintuitive approach to getting everything you want from your relationship - Ellis, Khadeen; Ellis, Devale, 1984-; Lakins, Leah (Rodale, 2023)
"After twelve years of marriage, twenty years together, and four kids, Devale and Khadeen Ellis have been through a lot. They've loved their way through a long-distance relationship, financial instability, parenthood, Khadeen's near-death, and their near-divorce, chronicling their day-to-day life with their boys online. After much trial and error, they hit upon one surprising, essential truth: If you're looking for a healthy relationship and a fulfilling life, focus on your partner's needs instead of your wants. Choosing service over selfishness will not only make your relationship stronger, but it will help you achieve your own goals and build a legacy together. With their trademark transparency and humor, Khadeen and Devale share the messy, behind-the-scenes work of what it takes to succeed and support one another in their search for individual purpose while growing in their marriage." -- Amazon.com.